Empirical Models for the Correlations Between Total Ozone Column and Latitude in different regions in IRAQ - Yonis, Firas hazem; AL-Rijabo, Waleed Ismeer Jasim (Journal of natural sciences, life and applied sciences, 2021)
This Research aimed at find a correlation between Total Ozone Column (TOC) and Latitude in different regions in Iraq using several Mathematical Models.Models were used for that [Linear Models, Quadratic Models, Exponential Models, Logarithmic Models, Power Models].Several statistical tests [R2, R, MAE, RMSE] were used to control the validation and goodness of these Models. Quadratic Model gave the highest R2 among the other models in all stations. R2 obtained between (TOC) & Latitude in Winter & Spring months were very high and ranged between (0.953 – 0. 976). Summer months show a good correlation in June & July and week correlation in August. In Autumn months a good correlation was obtained in October & November and week correlation was obtained in September. The highest R2 means that there is a highly significance correlations between Total Ozone Column and Latitude. This mean that these Models gave a very good results to estimate (TOC) from Latitude.
Keywords: NASA; Regression Models; IRAQ; Latitude; TOC; R2; MAE; RMSE